Social exclusion and psychopathology in LGBTQ+ communities: a neuropsychosocial review - Stergios Kaprinis; Anastasios Charalampakis (Frontiers in Sociology, 2025)
LGBTQ+ individuals are disproportionately affected by depression, anxiety, and suicidal ideation, primarily due to persistent social exclusion, prejudice, and systemic discrimination rather than any inherent psychopathology. This review synthesizes contemporary theoretical frameworks, including the Minority Stress Model, the Psychological Mediation Framework, and the Rejection Sensitivity Model, to examine the internalization of systemic marginalization and its manifestation as psychological distress. Significant mediators, such as internalized stigma, emotional dysregulation, and rejection sensitivity, are investigated alongside structural determinants, such as familial rejection and intersectional oppression. Contemporary insights from social psychology, psychiatry, and neuroscience were used in this study. Neurobiological data indicate that chronic minority stress modifies the limbic–prefrontal circuitry, disrupts the hypothalamic– pituitary–adrenal (HPA) axis, and increases allostatic load. The implications for clinical practice and public health were analyzed, emphasizing the importance of community-based resilience initiatives, inclusive policy reforms, and LGBTQ+-affirmative therapy. The article concludes by outlining the theoretical constraints and proposing future avenues for participatory and multidisciplinary studies.